Engineering Drawing Challenge II - Lamiroy, Bart; Lopresti, Daniel P. (Graphics Recognition. Current Trends and Evolutions, 2018)
The first GREC Engineering Drawing Challenge (http://iapr-tc10.univ-lr.fr/index.php/conferences/contest?id=297) was held in 2015. Since then, more than 800 high definition engineering drawings have been digitized and made available to the research community, accounting for approximately 400 GB of unique image data. The collection is available on the Lehigh University DAE server (http://dae.cse.lehigh.edu/DAE/?q=browse/dataitem/606796). The 2015 edition gave rise to a number of challenges and ideas specifically targeted to Graphics Recognition and were published in the proceedings of the GREC workshop. They are still relevant and open questions, and need to be addressed by the research community. This year, we are launching a complementary and different challenge...